1982
DOI: 10.1093/oxfordjournals.jbchem.a133799
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Biosynthesis in Brevibacterium flavum: Properties and Essential Role of O-Acetylhomoserine Sulfhydrylase

Abstract: Out of 27 strains of methionine auxotrophs of Brevibacterium flavum, 14 strains did not grow on homoserine but grew on O-acetylhomoserine, and all were found to lack homoserine O-acetyltransferase [EC 2.3.1.31] alone. Another 3 strains did not grow on O-acetylhomoserine but grew on homocysteine, and the two strains tested were found to lack O-acetylhomoserine sulfhydrylase (AHS) alone, without any changes in the activities of cystathionine gamma-synthase [EC4.2.99.9] and beta-cystathionase [EC 4.4.1.8]. Protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Cystathionine is then cleaved through the .-cystathionase reaction to produce L-homocysteine. Butin some microorganisms, O-acetylhomoserine can also be sulfhydrylated with H2S through catalysis by O-acetylhomnoserine sulfhydrylase, giving rise to Lhomocysteine directly (7,17,19,20,30,31).The enzyme homoserine O-acetyltransferase (EC 2.3. 1.31), which catalyzes transfer of the acetyl group from acetyl coenzyme A (acetyl-CoA) to the 0 atom of homoserine (see equation 1 below), also catalyzes the acetyl exchange reaction between O-acetylhomoserine and [14C]homoserine (see equation 2) (9, 23).…”
mentioning
confidence: 99%
“…Cystathionine is then cleaved through the .-cystathionase reaction to produce L-homocysteine. Butin some microorganisms, O-acetylhomoserine can also be sulfhydrylated with H2S through catalysis by O-acetylhomnoserine sulfhydrylase, giving rise to Lhomocysteine directly (7,17,19,20,30,31).The enzyme homoserine O-acetyltransferase (EC 2.3. 1.31), which catalyzes transfer of the acetyl group from acetyl coenzyme A (acetyl-CoA) to the 0 atom of homoserine (see equation 1 below), also catalyzes the acetyl exchange reaction between O-acetylhomoserine and [14C]homoserine (see equation 2) (9, 23).…”
mentioning
confidence: 99%
“…One is an OAH sulfhydrylase lacking CTT ␥-synthase activity of B. flavum that has no CTT ␥-synthase (23), and the other is a CTT ␥-synthase of Bacillus sphaericus (12), which also has an activity of OAH sulfhydrylase that is not functional to directly synthesize homocysteine in the cell. The increase in the synthesis of OAH sulfhydrylase with abundant cysteine (or glutathionine) in the medium is, therefore, considered to be a result of substrate induction of CTT ␥-synthase.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found activities of CTT ␥-synthase, CTT ␤-lyase, and OAH sulfhydrylase in a cell extract of an extremely thermophilic bacterium, Thermus thermophilus HB8, in addition to a very high OAS sulfhydrylase activity (35). On the other hand, Kosuge et al (17,18) have reported that T. thermophilus HB27 synthesizes homocysteine through direct sulfhydrylation of OAH and that transsulfuration is not func-tional, as reported for Saccharomyces cerevisiae (6) and Brevibacterium flavum (23), by demonstrating that mutant strains deficient in a gene homologous to S. cerevisiae MET17 require homocysteine but not CTT to grow. In order to determine which pathway is physiologically active for the synthesis of homocysteine in T. thermophilus HB8, transsulfuration or direct sulfhydrylation of OAH, we examined the activities of enzymes involved in the pathway leading to methionine in extracts of cells fed with various sulfur sources, and we estimated the amounts of the enzymes synthesized.…”
mentioning
confidence: 94%
See 2 more Smart Citations